2009
DOI: 10.5539/ass.v5n12p17
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Credit Card: Are Demographic Factors a Good Indicator?

Abstract: This study investigates on the relationship between demographic factors and the usage of Islamic credit card as well as Conventional credit card demonstrates their interdependencies. The debatable issues as been addressed by many authorities not only in terms of the numbers of credit card flooding the nation's economy, but the amount of transactions that end up with payment default and the numbers of credit card fraud as been recorded which threatened the economy should be seriously focused. Nevertheless the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 16 publications
(11 reference statements)
1
28
0
1
Order By: Relevance
“…Only few studies have examined the Islamic credit card usage intention (Mansor and Che-Mat, 2009;Choo et al, 2007). The magnitude to investigate the Islamic credit card usage intention is a worthy undertaking in order to fill the research gap.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have examined the Islamic credit card usage intention (Mansor and Che-Mat, 2009;Choo et al, 2007). The magnitude to investigate the Islamic credit card usage intention is a worthy undertaking in order to fill the research gap.…”
Section: Introductionmentioning
confidence: 99%
“…The vast literature on demographic factors (age, education, gender and income) declared that these demographic items have an important effect on the adoption and usage of different products, services and innovations even in context of Islamic banking services. These factors have also been tested regarding adoption and usage of Islamic credit card, although the number of these studies has been few (Mansor and Che Mat, 2009, Dali and Rais, 2006, Amin, 2012 and more importantly, partially conflicting results have been achieved in these studies. The below table indicate to summary of these studies which indicated to the importance of demographic items regarding the acceptance and usage of Islamic and non-Islamic banking services.…”
Section: Islamic Banking and Demographic Itemsmentioning
confidence: 99%
“…Adoption of e-banking (Wong et al, 2010, Gan et al, 2006, Agarwal et al, 2009, Adoption intention of retail selfservice checkouts (Lee et al, 2010), Adoption of internet and online banking (Lassar et al, 2005;Pikkarainen et al, 2004) Adoption of internet (Nayak et al, 2010, Pan andMarsh, 2010) Adoption intention of 3G (Chong et al, 2011) Usage of Islamic banking products and services (Metawa and Almossawi, 1998) Islamic banking services preference (Ahmad et al, 2011, Ahmad et al, 2008 Islamic credit card usage and selection (Mansor and Che Mat, 2009, Dali and Rais, 2006, Amin, 2012…”
Section: Constructmentioning
confidence: 99%
“…The introduction of ICCs is a part of the Islamic banking industry development to avoid the interest linked financial instruments of the conventional banking which Muslims are prohibited in dealing. ICCs have become more established in 2002 with the launch of BIMB's ICC or Bank Islam Card [6]. Subsequently, various other financial institutions such as Bank Simpanan Nasional, Maybank, CIMB, and HSBC have come up with their own unique ICCs.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Interestingly, in response to the new entry of ICCs into the Malaysian market, several studies have been carried out. For instance, a study by Mansor and Che-Mat [6] found that CCCs were preferably used by consumers compared to ICCs. This finding was further supported by Choo et al [16] who revealed the limited ownership of ICCs among Malaysians.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%